Proposta pedagógica para a inserção da perspectiva da conservação da flora para o ensino de Ciências - Russo, Cristiane Rodrigues Menezes (2014)
The State of Amapá has about 70% of its territory in protected areas, creating a peculiar feature of conservation. Within this landscape, is the science education as key driver in promoting a sustainable approach in the use of natural resources through the usual technical and knowledge of plants. In this scenario, the municipality of Serra do Navio has a vocation for environmental and adventure tourism on the natural scenic beauty, in which the creation of an area to be used by the population for the purpose of enhancing the natural and cultural heritage, contribute to the development integral of the region. Currently, the educational landscape of the city does not differ from national reality and, although it is undisputed that environmental issues should be among the priority issues in modern society and educational activities outside of the classroom are an efficient instrument for the establishment of a new perspective on the relationship between man and nature, there is a lack of educational spaces dedicated to this theme. Several studies highlight the importance of green or natural areas for the development of educational activities for the Science Teaching, which are held several actions that can be provided interpretive trails to sensory gardens. The objective of this research was to investigate teachers' knowledge about the flora in the city of Serra do Navio and identify educational resources adopted for the botanical content in elementary school proposing the introduction of new teaching tools. This research was divided into three stages: the first for the theoretical research and practice; the second for the collective construction of a pedagogy for teaching Botany; and the third for the creation of architectural design for the Sensory Garden Tumucumaque and partnerships. The subjects are public school teachers in the city of Serra do Navio. Research in this research is qualitative, characterized by the acquisition of descriptive data obtained in direct contact with the researcher studied the situation, trying to emphasize more the fundamentals and methods of the product, and worrying in portraying the expectation of the participants relating to matters involved in educational research. The object of research has to do with teaching, learning and the context (categories of analysis and research), considering their interrelationships in science education for the Amazon region. The results obtained in this study it was found that the prior knowledge of teachers for the Botany content are appropriate to the principles of significant learning proposed by Ausubel, and executed collaborative activities resulted in the construction of the educational proposal for the teaching of Botany in the Sensory Garden Tumucumaque defining the objectives and competencies for each level of basic education, emphasizing the aspects related to flora conservation using the knowledge of medicinal plants as subsumer. In this respect the Ethnobotany is configured as an important source of social and environmental information to help the teacher in obtaining the necessary conditions to promote meaningful learning. The Sensory Garden Tumucumaque can be an early organizer of the comparative type for teaching botany, to present family floristic elements to students, while bringing scientific information related plants. The appreciation and understanding of the mechanisms behind the science education experiences in natural environments can bring out important goals for education related to scientific knowledge of the region.